2016
DOI: 10.1371/journal.pone.0167001
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Serum Protein Analysis Identifies Novel Biomarkers of Advanced Fibrosis in Patients with Chronic Liver Disease with the Potential to Improve Diagnostic Accuracy of Established Biomarkers

Abstract: Background and AimsNon-invasive markers of liver fibrosis are urgently required, especially for use in non-specialist settings. The aim of this study was to identify novel serum biomarkers of advanced fibrosis.MethodsWe performed an unbiased screen of 120 serum analytes including cytokines, chemokines and proteases in 70 patients (35 without fibrosis, 35 with cirrhosis on biopsy), and selected a panel of 44 candidate biomarkers, which were subsequently measured in a mixed-etiology cohort of 432 patients with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 31 publications
2
42
0
4
Order By: Relevance
“…our study for the first time demonstrates its utility as a circulating PDAC biomarker in patients (Bennewith et al, 2009;Neesse et al, 2011). Both MMP7 and CCN2 have been associated with poor prognosis in different types of cancer (Klupp et al, 2016;Sun et al, 2017) and with fibrotic or inflammatory diseases (Dendooven et al, 2011;Irvine et al, 2016). However, our results suggest that an improvement in the specificity of MMP7 and CCN2 results from the inclusion of additional biomarkers.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…our study for the first time demonstrates its utility as a circulating PDAC biomarker in patients (Bennewith et al, 2009;Neesse et al, 2011). Both MMP7 and CCN2 have been associated with poor prognosis in different types of cancer (Klupp et al, 2016;Sun et al, 2017) and with fibrotic or inflammatory diseases (Dendooven et al, 2011;Irvine et al, 2016). However, our results suggest that an improvement in the specificity of MMP7 and CCN2 results from the inclusion of additional biomarkers.…”
Section: Discussionmentioning
confidence: 62%
“…Both MMP7 and CCN2 have been associated with poor prognosis in different types of cancer (Klupp et al , ; Sun et al , ) and with fibrotic or inflammatory diseases (Dendooven et al , ; Irvine et al , ). However, our results suggest that an improvement in the specificity of MMP7 and CCN2 results from the inclusion of additional biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported MMP-7 as a diagnostic or prognostic marker for various malignancies, including cholangiocarcinoma, pancreatic carcinoma, and gastric cancer, as well as fibrosis of lung and liver (3539). Of specific relevance to our findings, MMP-7 was previously reported as elevated in serum and liver samples from subjects with BA after surgical treatment (40, 41), correlating with the severity of fibrosis regardless of the degree of jaundice clearance (41).…”
Section: Discussionmentioning
confidence: 99%
“…The increased presence of MMP‐7 in human serum has been implicated in the pathogenesis of acute and chronic inflammatory conditions of the liver . Thus, we measured the serum levels of MMP‐7 in three group of mice.…”
Section: Resultsmentioning
confidence: 99%
“…The increased presence of MMP-7 in human serum has been implicated in the pathogenesis of acute and chronic inflammatory conditions of the liver. (28,29) Thus, we measured the serum levels of MMP-7 in three group of mice. At 2 weeks postinoculation higher levels of MMP-7 (P < 0.0005) were detected in serum of T R(VP2,VP4)inoculated mice than saline-inoculated controls (Fig.…”
Section: Increased Mmp-7 Serum Levels In T R(vp2vp4) -Inoculated Micementioning
confidence: 99%